Utilization of interactive multimedia to improve learning interest and learning achievement of child - Agatha Devian Primamukti; Muh Farozin (Jurnal Prima Edukasia, 2018)
This research aimeds to find out (1) the effect of interactive multimedia on the learning interest, (2) the effect of interactive multimedia on the learning achievement, (3) the different effect of interactive multimedia and image media on the learning interest and learning achievement of grade IV students of elementary schools in Wonosari Gunungkidul. This research was a quasi experimental. The design which was used was pretest-postest control group design with two experimental groups taught by using interactive multimedia and one control group using the image media. The data analysis used the paired sample t-test and independent sample t-test. The result of the research showed that: (1) there was an effect of interactive multimedia on the learning interest at the significance level of 0.000 0.05, (2) there was an effect of interactive multimedia on the learning achievement at the significance level of 0.000 0.05, and (3) the big different effect of interactive multimedia and image media on the learning interest and learning achievement was the learning interest with the gained score 10.412 for the experimental class 1 and 13.004 the experimental class 2, and the learning achievement with the gained score 8.703 the experimental class 1 and 6.810 the experimental class 2.